PENGARUH MODAL DAN TENAGA KERJA TERHADAP PENDAPATAN HOME INDRUSTRI SEPATU DI KABUPATEN SIDOARJO (STUDY KASUS DI KECAMATAN KRIAN) - ROSIDI, ABDUL MAJID; SUPARNO, SUPARNO (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2018)
ABSTRACTSmallEandEMediumEEnterprises (SMEs) is one of the economi sectors whosesrolesis very large to the economy in indonesia, especiallysinsthesabsorptionsofsmanpower.Analysist oft variabel variablest thattaffectT the income of shoet indrustry home in sidoarjo regency (Case Study of Krian Subdistrict) tThis studyt aims to find outt variable variables that affectt the income of shoes tin krian tdistrict, where thetTcraft is stillTable tot competeTand suvivet so it can serve as one of strategict businesssin achieve economic growth. Thespopulationn in this study is basedn on statistical datan obtained (Krian District office) and use sample based on cross section data obtaineds from respondents.Can be seenn the significantn value of capital (x1) is equal ton 0,905 greater than 0,05 andn the value of tarithmeticn is equal to 0,120 smallern than t table 2,01410 it cann besconcludedsH1 rejected. Thatsmeansscappitals(x1) n has no effect on incomen then seen significantn value of labor (x2) n is equal to 0,001 smaller than 0,05 andn the calculatedn value is 3.708 largern than t tablen 2,01410sitscan be councludedn H2 receivedn meaning thatn labor (x2) has an positivesandn significantson income (Y).Â Â Keywords: Modal, Tenaga Kerja, Pendapatan